Pengaruh Quality Of Work Life (Qwl) terhadap Kinerja Pegawai di Bank Danamon Syariah Makassar - Syarif Al Qadri; Moh. Yasin Soumena; Muhammad Kamal Zubair (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2020)
This study discusses the influence of Quality of Work Life conducted by Bank Danamon Syariah Makassar. Quality of Work Life is a management concern about how work can affect humans, organizational effectiveness and the importance of employee participation in decision making processes, especially those related to career, income and time. front of them in their work. The purpose of this research is to find out whether the effect of Quality of Work Life consisting of Rewards System, Work Environment, and Work Restructuring variables influences employee performance. And to find out the dominant variables simultaneously influencing. This research is a quantitative research with descriptive method. The data collection is done through the distribution of questionnaires. The method used to test hypotheses is to use Validity Test, Reliability Test, Normality Test, Multiple Regression Analysis, T Test, F Test, Adjusted R Square, and Double R Correlation. Linear regression test results, Y = 11,976 + 0.488 x 1 + 0.081 x 2 + 0.033 x 3, it can be concluded that the variable X1 is the Rewards System that has a value of 0.488 and has a positive and significant effect on employee performance variables (Y), variable X2, namely Environment Work with a value of 0.081 does not have a positive and significant effect on the Employee Performance variable (Y), variable X3, namely Work Restructuring, which has a value of 0.033, does not have a positive and significant effect on the employee performance variable (Y). The results of this study indicate: based on the t (partial) calculation of the reward system, the calculated value is 3.450 and the value (sig) = 0.002 is smaller than the probability value that is 0.05 or 0.002 <0.05, meaning that the dominant reward system variable has a positive and significant effect on employee performance at Bank Danamon Syariah Makassar. T-test results (partial) work environment obtained a calculated value of 0.650 and (sig) = 0.521 greater than the probability that is, 0.05 or 0.521> 0.05 means that the work environment variable does not affect the performance of employees at Bank Danamon Syariah Makassar. And the t-test results (partial) work restructuring obtained a calculated value of 0.239 and (sig) = 0.813 greater than the probability of 0.05 or 0.813> 0.05 which means the work restructuring variable has no effect on employee performance at Bank Danamon Syariah Makassar